Pengembangan Kepimpinan: Meningkatkan Jiwa Kepemimpinan Inovatif dan Berintegritas di SMK Al-Qur’an dan Dakwah Alam Kongbeng - Hartono, Hartono; Fahruddin, Achmad; Prasetyo, Totok Adhi (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve students' understanding, motivation, and leadership character through a seminar entitled "Improving Innovative and Integrity-Based Leadership." The seminar was held on November 11, 2024, at the Al-Qur'an and Da'wah Alam Vocational School, Kongbeng District, East Kutai Regency, involving 82 student council administrators from junior high schools (SMP/MTs) and vocational high schools (SMK). The activity was carried out for a full day using a participatory approach that included planning, implementation, evaluation, and follow-up stages. Data were collected through observation, short interviews, and documentation, then analyzed thematically. The results showed a high level of participation (95% attendance) and active participant interaction during the discussion. This seminar increased participants' understanding of the concept of innovative leadership, fostered an attitude of integrity, and strengthened intrinsic motivation to lead honestly, creatively, and responsibly. Furthermore, this activity established a collaborative forum between schools as a form of sustainability for the development program. Practically, this seminar contributed to strengthening student leadership character and can serve as a model for replication of leadership development activities in East Kutai and other regions.